Vaccination in older adults with cancer and older cancer survivors - Alejandro Arreola-Rodríguez; Juan Pablo Negrete-Najar; Enrique Soto-; Ana Patricia Navarrete-Reyes (Brazilian Society of Geriatrics and Gerontology, 2021)
Vaccination is one of the most effective means of preventing infections and should be widely promoted, especially in immunocompromised patients, such as older adults with cancer and older cancer survivors. However, adherence is low, which is due in part to lack of awareness, fear of side effects, hesitancy to vaccinate and rejection of vaccination, especially for COVID-19. The objective of this paper is to clarify current indications for vaccination in these populations and underscore its importance.